Manajemen Mutu Perguruan Tinggi di Universitas Islam Negeri Syarif Hidayatullah Jakarta - Lolytasari Lolytasari (At-Tajdid: Jurnal Ilmu Tarbiyah, 2019)
This study examines the quality management of universities at the Syarif Hidayatullah State Islamic University Jakarta. In managing a university, it has its own uniqueness that manages knowledge as a college asset, so the focus of this research is the knowledge management implemented by Syarif Hidayatullah State Islamic University Jakarta? The method used in this study uses qualitative methods. The conclusion of this study is about the plan of Syarif Hidayatullah State Islamic University in Jakarta to implement knowledge management as its core business. However, it needs to be improved: increasing access to knowledge management units and increasing inventory of special collections consisting of historical knowledge manuscripts and archives as a source of knowledge needed by researchers and academicians. Syarif Hidayatullah Jakarta is headed for a World Class University, one program that needs to be made specifically is knowledge management that manages explicit knowledge and tacit knowledge. This program requires the human resources needed.